Evaluating the level of satisfaction of patients utilizing first-level health facilities as a function of health system performance rating in the province of Elazig, Turkey - Bulut, Aliye; Oguzoncul, A. Ferdane (Dove Medical Press Ltd, 2014)
Purpose: This study was conducted to determine the level of satisfaction of patients utilizing first-level health care facilities as a function of health system performance rating in Elazig province of Turkey. Methods: The study was conducted between December 2013 and March 2014 at the family health centers in the Elazig province center. For collecting the data in the cross-sectional study conducted with 1,290 patients, personal data form for patients and the Turkish version of European Patients Evaluate General/Family Practice scale was used. Results: Of the patients who participated in the study, 54.3% were female. According to the general average scores received by the patients from European Patients Evaluate General/Family Practice-TR Patient Satisfaction Survey questions, average scores of male patients were found to be higher than those of female patients. Scores of the divorced and widow patients were higher compared to other groups, but this was not statistically significant. Average scores of the patients whose educational status is secondary school were higher compared to other groups. Scores of the patients with children were higher compared to those without children. Scores of the patients whose occupation was farming were higher compared to the other groups of occupation. Scores of the patients whose income was TL 1,001-2,500 were found to be higher compared to other patients. Scores of the patients who stated that they never had difficulty in access were higher compared to others, but this was not statistically significant. Average scores of the patients who had chronic diseases and patients who stated to have physical handicap were higher compared to those who did not have chronic disease and physical handicap, but these differences were not found to be statistically significant, either. Conclusion: There is a statistically significant difference between the patients' demographic characteristics (sex, educational status, occupation, and income status) and their levels of satisfaction with the family medicine practice.
Keywords: patient satisfaction; primary care; EUROPEP